2016
DOI: 10.18051/univmed.2015.v34.43-51
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl p-methoxycinnamate from Kaempferia galanga inhibits angiogenesis through tyrosine kinase

Abstract: BACKGROUND<br />Many tumors express on their receptor tyrosine kinases vascular endothelial<br />growth factor activity associated with angiogenesis. Inhibition of<br />angiogenesis through reduction of tyrosine kinase activity is a promising<br />strategy for cancer therapy. The present study aimed to determine the<br />mechanism and potency of ethyl p-methoxycinnamate (EPMC) isolated<br />from Kaempferia galanga as angiogenesis inhibitor.<br />METHODS<br />A la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…In addition, we also collected the blood vessels of CAM in the formalin buffer and carried out microscopic observations of the histopathologic slide of the CAMusing Hematoxylin and Eosin (HE) staining. To confirm the antiangiogenic activity, this CAM assay was achieved with certain alteration as explained before 18,20 . The growth of the endothelial cell in the neovascular capillaries wasexposed in CAM cross-sections by an inverted phase contrast microscope, Nikon H600L.…”
Section: Cam Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we also collected the blood vessels of CAM in the formalin buffer and carried out microscopic observations of the histopathologic slide of the CAMusing Hematoxylin and Eosin (HE) staining. To confirm the antiangiogenic activity, this CAM assay was achieved with certain alteration as explained before 18,20 . The growth of the endothelial cell in the neovascular capillaries wasexposed in CAM cross-sections by an inverted phase contrast microscope, Nikon H600L.…”
Section: Cam Assaymentioning
confidence: 99%
“…Docking of FA molecule into each of the 3D structure of proteins was performed as described in our previous study 20 . The best docking results can be noticed by relating the structure of the docked FA molecule with the crystal structure of reference ligand in the binding site.…”
Section: In Silico Assaymentioning
confidence: 99%
“…Umar et al (2012) reported that EPMC has a mechanism to inhibit COX1 and COX2. In the treatment of inflammation with kencur extract in the medical world, it was reported that kencur extract has the same effect as one of the non-steroidal anti-inflammatory drugs (NSAIDs) namely meloxicam (Ekowati et al, 2015 ;Syahruddin et al, 2017).…”
Section: Inhibition Of Protein Denaturationmentioning
confidence: 99%
“…in vitro untuk aktivitas antiangiogenesis yang melibatkan hambatan enzim COX-2 berkolerasi linier dengan metode rat aortic ring assay (Umar et al, 2014), Chick Chorioallantoic Membrane (CAM) Assay (Ekowati et al, 2015;Hamid et al, 2013) dan Matrigel Assay (Donovan et al, 2001 (Meuth, 2010;Ruswanto, 2013;Putra et al, 2016). dan perkembangan sel kanker payudara (Suvannang et al, 2011;Dai et al, 2010;Winer at al., 2005;Wakeling at al., 2000).…”
Section: Beberapa Penelitian Melaporkan Bahwa Ujiunclassified